2010
DOI: 10.1103/physrevb.81.024117
|View full text |Cite
|
Sign up to set email alerts
|

Binding in alkali and alkaline-earth tetrahydroborates: Special position of magnesium tetrahydroborate

Abstract: Compounds of light elements and hydrogen are currently extensively studied due to their potential application in the field of hydrogen or energy storage. A number of new interesting tetrahydroborates that are especially promising due to their very high gravimetric hydrogen content were recently reported. However, the determination and understanding of their complex crystalline structures has created considerable debate. Metal tetrahydroborates, in general, form a large variety of structures ranging from simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 72 publications
7
34
0
Order By: Relevance
“…10 Both polymorphs have unexpectedly complex crystal structures, which differ significantly from the numerous theoretical predictions (see Ref. 11 and references therein). Interestingly, α‐Mg(BH 4 ) 2 contains 6.4 % unoccupied voids (each of 37 Å 3 ) in the structure 9.…”
Section: Specific Densities (ρ) Of Mg(bh4)2 Polymorphs and Their Gravmentioning
confidence: 88%
“…10 Both polymorphs have unexpectedly complex crystal structures, which differ significantly from the numerous theoretical predictions (see Ref. 11 and references therein). Interestingly, α‐Mg(BH 4 ) 2 contains 6.4 % unoccupied voids (each of 37 Å 3 ) in the structure 9.…”
Section: Specific Densities (ρ) Of Mg(bh4)2 Polymorphs and Their Gravmentioning
confidence: 88%
“…The electrochemical oxidative stabilities measured on platinum, stainless steel, and glassy carbon electrodes were 1.7, 2.2, and 2.3 V, respectively (Figure S7). These results showed that for the first time: 1) Mg(BH 4 ) 2 is electrochemically active in THF, that is, ionic conduction is possible, and 2) reversible magnesium deposition/stripping from an inorganic, relatively ionic (Mg Bader charge is +1.67) [7] and halide-free salt is feasible. Although these results are promising, to make this electrolyte more practical for use in batteries the electrochemical performance needs to be improved by lowering the overpotentials, and achieving higher current density and coulombic efficiency.…”
mentioning
confidence: 79%
“…This behavior has been discussed in greater detail in literature. 47 Additionally, Table II lists the average contact distance between magnesium and borohydride hydrogens. In this study, we differentiate between hydrogens in direct contact with magnesium, which are denoted Hb, as in "bridging" hydrogens, from terminal hydrogens, Ht.…”
Section: Resultsmentioning
confidence: 99%